Microstructure and mechanical properties of friction welded joints of a fine-grained hypereutectoid steel with 4% Al - Özdemir, N; Orhan, N (Elsevier Science Sa, 2005)
In this study, joining characteristic of a fine-grained hypereutectoid ultra-high-carbon steel (UHCS) with thermo-mechanical cycle was investigated by the friction welding process. The joining performances of UHCS/UHCS friction welded joints were studied, and the influences of welding parameters (friction pressure, forging pressure, friction time, forging time and rotational speed) on the microstructure and mechanical properties of the welded joints were also estimated. The microstructural properties of the heat-affected zone (HAZ) were examined by optical and scanning electron microscopy (SEM). The microhardness across and perpendicular to the interface were measured and the strength of the joints was determined with tensile tests. The results were evaluated considering the microstructures formed during welding, The experimental results indicate that each parameter has a little individual effect on the quality of the joint but the combined effect of the rotation speed, friction pressure and friction time has a significant effect on the mechanical and metallurgical properties. Especially, by choosing rotation speed, friction pressure and friction time properly, it is possible to increase the quality of joint. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: solid-state welding friction; friction welding; hypereutectoid steel